2015
DOI: 10.1016/j.thromres.2015.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Von Willebrand factor-A1 domain binds platelet glycoprotein Ibα in multiple states with distinctive force-dependent dissociation kinetics

Abstract: Circulating von Willebrand factor (VWF) adopts a closed conformation that shields the platelet glycoprotein Ibα (GPIbα) binding site in the VWF-A1 domain. Immobilized at sites of vascular injury, VWF is activated by its interaction with collagen and the exertion of increased hemodynamic forces. Studies on native VWF strings and isolated A1 domains suggest the existence of multiple A1 binding states in different biophysical contexts. In this single-molecule study, we have used a biomembrane force probe (BFP) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 46 publications
3
66
2
Order By: Relevance
“…The apparent rates of association and dissociation of G1324A and G1324S from collagen are very similar yielding binding affinities that are at most 2-3-fold different in K D values than WT A1 and still within experimental error. Contrary to previous reports that claim that collagen induces a conformational change in A1 upon binding (33) and that G1324S impairs this conformational change (34), we do not observe significant differences in the dissociation rates of these type 2M variants relative to WT A1 that would result from conformation-dependent collagen-binding interactions. The increase in thermodynamic stability caused by G1324A and G1324S significantly reduces the probability of populating intermediate conformations that would have altered affinities for collagen.…”
Section: Discussioncontrasting
confidence: 99%
“…The apparent rates of association and dissociation of G1324A and G1324S from collagen are very similar yielding binding affinities that are at most 2-3-fold different in K D values than WT A1 and still within experimental error. Contrary to previous reports that claim that collagen induces a conformational change in A1 upon binding (33) and that G1324S impairs this conformational change (34), we do not observe significant differences in the dissociation rates of these type 2M variants relative to WT A1 that would result from conformation-dependent collagen-binding interactions. The increase in thermodynamic stability caused by G1324A and G1324S significantly reduces the probability of populating intermediate conformations that would have altered affinities for collagen.…”
Section: Discussioncontrasting
confidence: 99%
“…on May 11, 2018. by guest www.bloodjournal.org From dissociation rate. [20][21][22] Thus, we explored whether free Hb also directly interacts with the A1 domain, and determined that binding occurs with an equilibrium dissociation constant (K D ) 5 14.8 6 8.8 mM (supplemental Figure 3), possibly explaining the increase of VWFmediated platelet adhesion when the level of free Hb is $50 mg/dL (or 30 mM). A recent study reported that levels of free Hb $50 mg/dL may predict mortality in patients on ECMO, 23 and this level correlates with the threshold observed for platelet adhesion in our flow-dependent assay (supplemental Figure 1A).…”
Section: Flow Assaysmentioning
confidence: 99%
“…It appears possible that free Hb binds to the A1 domain when the A1A2 interaction in VWF is dissociated as a consequence of stretching forces or immobilization onto various surfaces. [13][14][15] Thus, A1 binding to Hb, like collagen and botrocetin, may induce a conformational change that increases the surface available for interaction with GPIba, 20 and/or the Hb bound to the A1 domain forms a new and stronger interface for GPIba binding. 22 In fact, the binding of the more active A1(R1450E)A2A3 mutant 18 to GPIba was slightly increased by free Hb (supplemental Figure 4).…”
Section: Flow Assaysmentioning
confidence: 99%
“…Recent studies propose that collagen binding via the A1 domain induces a conformational change in A1 that enables tighter binding to platelet GPIbα [4]. The linkage principle, referred to as ”affinity up-regulation”, is an example of positive coupling such that collagen binding preferentially induces a shift in equilibrium of the A1 domain to a platelet binding competent conformation with higher affinity for GPIbα.…”
Section: Introductionmentioning
confidence: 99%